Method for evaluating component uniformity of titanium alloy cast ingot
By using single-phase zone high-temperature solution and low-temperature aging processes in titanium alloy ingots, the ingot riser forms an α phase that is easy to detect, which solves the problems of complex detection process, poor accuracy and high cost in the prior art. , achieving high accuracy and low cost ingredient uniformity evaluation.
Patent Information
- Application Number
- CN202411366011.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-29
AI Technical Summary
In the prior art, the uniformity detection process of titanium alloy ingot components is complex, the accuracy is poor, and the evaluation cost is high. It is impossible to directly detect the α phase in the ingot. It requires multiple forging to obtain the α phase before testing, which adds the detection process and cost and can cause organizational deterioration.
Using the single-phase zone high-temperature solid solution, the first-stage low-temperature aging, β-spot heat treatment and the second-stage low-temperature aging, the ingot riser forms an α phase in an easy-to-detect equiax or short rod form, and passes high-low-scale tissue detection. Accurately evaluate the uniformity of the ingot composition.
It improves the accuracy of the evaluation of the uniformity of the ingot composition, reduces the difficulty and cost of testing, avoids organizational deterioration, simplifies the testing process, and improves the testing efficiency and economic benefits.
Smart Images

Figure CN119413548A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy detection, and in particular to a method for evaluating the uniformity of components of a titanium alloy ingot. Background Art
[0002] Titanium alloys have high specific strength, good ductility and good fracture toughness, and their market share in the aerospace field is increasing. Among them, near-β and β titanium alloys are widely used in the manufacture of important load-bearing components such as aircraft landing gear, main beams, and rotating shafts due to their high strength and toughness. However, the strengthening effect of this type of titanium alloy depends largely on the alloying effect of elements such as Cr, Fe, and Mo. Common titanium alloys of this type include: TC17 (Ti-5Al-4Mo-4Cr-2Zr-2Sn), TB6 (Ti-10Al-2Fe-3V), Ti-55531 (Ti-5Al-5Mo-5V-3Cr-1Zr), etc. Most of the elements in the aforementioned alloying effect are β-stabilizing elements. In the production process of the aforementioned types of titanium alloys, the difference in solid / liquid solubility will lead to macro- and micro-segregation problems. The increase in local element content caused by micro-segregation will strongly reduce the local phase transformation point T β , while titanium alloys are usually in (T β -50℃)~(Tβ+30℃)this narrow range is forged, so when T β When changes occur, the organizational properties of titanium alloys will be significantly affected. Therefore, in the production process of titanium alloys, evaluating the microsegregation level of elements such as Cr, Fe, and Mo is particularly critical for the production and application of this type of titanium alloys.
[0003] Since the microscopic deviation scale is usually at the millimeter level and there are no obvious identification features, it is impossible to evaluate the microscopic segregation level by detecting the chemical composition. Therefore, the existing technology usually uses the detection of α phase content to evaluate the local phase transition point of titanium alloy. The specific principle is: the α phase content has the characteristic that the closer to the phase transition point, the less the content. Therefore, when the α phase content is normal in most parts of the titanium alloy product and the local α phase content is very small or close to 0, it means that the local phase transition point is low, that is, Cr, Fe, Mo and other elements gather here, and bright spots appear on the low-magnification structure. This detection method is called "β spot inspection" in the industry. However, in the actual detection process, since there is no α phase in the structure of the titanium alloy ingot, it is impossible to directly perform β spot inspection. During the detection process, it is generally necessary to obtain the α phase through multiple forgings before testing, which increases the detection process and detection cost, and may cause structural deterioration during the forging process, affecting the accuracy of the detection; or the detection is performed on the finished bar, but in this way, since the bar has been prepared, if the detection and evaluation show that the ingot composition is poorly uniform, it will cause material scrapping and waste the cost of forging the finished bar. Summary of the invention
[0004] The present invention aims to provide a method for evaluating the uniformity of the composition of a titanium alloy ingot, so as to solve the problems in the prior art of complex detection process, poor accuracy and high evaluation cost during the detection of the uniformity of the composition of a titanium alloy ingot.
[0005] To solve the above problems, the present invention adopts the following technical solution: A method for evaluating the uniformity of the composition of a titanium alloy ingot comprises the following steps: Step 1: High temperature solid solution in single phase region, heat the ingot riser to T β + (10~300)℃, rapid cooling after heat preservation; Step 2: First stage low temperature aging: the ingot riser cooled in step 1 is placed at T β - Keep warm below (200~400), then raise the temperature to T β - (30~60)℃, keep warm and then cool; Step 3: β spot heat treatment: the ingot riser cooled in step 2 is placed at T β Keep warm at -25℃ and then cool; Step 4: Second stage low temperature aging, the ingot riser after water cooling in step 3 is kept at 600-650°C and then cooled; Step 5: High and low magnification tissue detection.
[0006] The principle of this scheme is: in step one, the ingot riser is rapidly cooled after solid solution in the single-phase region, so that the structure of the ingot riser becomes a supersaturated solid solution. In the heating process after the first stage of low-temperature aging in step two, due to the extremely large free energy difference, the driving force for the nucleation of the new phase is greatly increased, and the interface of the new phase is changed from a semi-coherent interface to an incoherent interface with higher interface energy. The α phase with the incoherent interface will spontaneously geochemically form an equiaxed or short rod α phase, so that the ingot riser has the basic conditions for β spot detection, and then the β spot heat treatment in step three and the second stage of low-temperature aging in step four are used to form the ingot riser to detect the α phase state, and finally in the high and low magnification structure detection in step five, the equiaxed or short rod α phase is conveniently and clearly detected and observed, thereby accurately evaluating the uniformity of the ingot composition.
[0007] The beneficial effects of this program are: 1. High accuracy of ingot composition uniformity assessment: Compared with the prior art that requires multiple forgings to obtain equiaxed or short rod-shaped α phases for better observation and identification, not only is the process more complicated, but the internal structure of the titanium alloy will deteriorate during the multiple forging process, affecting the accuracy of the ingot composition uniformity assessment. In this application, through high-temperature solid solution in the single-phase region and the first-stage low-temperature aging process, the ingot riser is formed with an equiaxed or short rod-shaped α phase, which effectively improves the display degree in the subsequent α phase detection process, which can not only effectively reduce the difficulty of detection, but also avoid the formation of lamellar α phases, improve the recognition of α phases, and be easy to identify at both high and low magnification scales, thereby more accurately evaluating the composition uniformity of titanium alloy ingots.
[0008] 2. Higher process feasibility: Compared with the detection method in the prior art, the detection process requires multiple forgings, which is not only complicated, but also causes the internal structure of the titanium alloy to deteriorate during the multiple forging process, affecting the accuracy of the ingot composition uniformity assessment. The detection process in this application does not require multiple forgings, and can make the ingot riser form an alpha phase with an easily identifiable equiaxed or short rod shape, which not only improves the accuracy of the assessment, but also makes the process simpler and more feasible, and the detection cost is also lower.
[0009] 3. Ability to complete the inspection efficiently: In this application, since the ingot riser is treated by heat treatment process, it does not need to spend a lot of time on forging, etc., which effectively improves the evaluation and inspection efficiency, helps to shorten the titanium alloy production cycle and obtain better economic benefits.
[0010] 4. Good economic benefits: By directly detecting β spots on ingots, the reliability of the smelting process and the level of product segregation can be quickly evaluated. Compared with conventional finished bar testing, it effectively saves about 100,000 yuan in forging costs and material loss per furnace, and avoids the scrapping of ingots (the cost of ingots per furnace is 300,000 to 500,000 yuan).
[0011] Preferably, as an improvement, in step 1, the insulation time of the ingot riser is T1=D×(0.5-3.0) minutes, wherein D is the thickness of the riser, in mm.
[0012] Preferably, as an improvement, in step 2, the ingot riser is at T β -The holding time at (200~400)℃ is 1~8h.
[0013] Preferably, as an improvement, in step 2, the ingot riser is heated to T β -After (30~60)℃, the holding time is T2=D×(0.5~3.0) minutes, where D is the thickness of the riser in mm.
[0014] Preferably, as an improvement, in step 3, the ingot riser is at Tβ The holding time at -25°C is 2h.
[0015] Preferably, as an improvement, in step 4, the ingot riser is kept at a temperature of 600-650° C. for 4-8 hours.
[0016] Preferably, as an improvement, the rapid cooling method in step one is water cooling.
[0017] Preferably, as an improvement, in step 2, the ingot riser is heated to T β - (30~60)℃ insulation and cooling method is air cooling.
[0018] Preferably, as an improvement, in step 3, the ingot riser is at T β After keeping at -25℃, the cooling method is water cooling.
[0019] Preferably, as an improvement, in step 4, the ingot riser is cooled by air after being kept at 600-650°C.
[0020] The beneficial effects of this program are: 1. In this scheme, the thickness of the ingot riser is used to determine the insulation time of the single-phase high-temperature solid solution in step 1 and the heating time to T in step 2. β -The holding time after (30~60)℃ is conducive to the ingot riser to more fully complete the spheroidization transformation of the α phase and fully form the equiaxed or short rod shaped α phase, so as to facilitate subsequent convenient and accurate detection.
[0021] 2. The rapid cooling method in step 1 is set to water cooling, so that the riser of the ingot after high-temperature solid solution is rapidly cooled, which facilitates the formation of a supersaturated solid solution, greatly increases the momentum of the α phase precipitation in step 2, and changes the morphology of the precipitated phase.
[0022] 3. Since the phase transition point of the titanium alloy was not detected before the uniformity of the ingot composition was tested and evaluated, the temperature value of the β-spot heat treatment in step three could not be accurately determined. The ingot riser could only be trial-produced using the empirical average phase transition point of the corresponding type of titanium alloy. The heat treatment temperature value of the β-spot heat treatment in step three was adjusted based on the trial results, and a characteristic β-spot detection result was obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a high-magnification tissue photograph after the completion of step 2 in embodiment 1 of the present invention.
[0024] Figure 2 This is a high-magnification microstructure photograph of a conventional finished rod in a comparative example of the present invention.
[0025] Figure 3This is a low-magnification tissue photograph after step five in Example 1 of the present invention is completed.
[0026] Figure 4 This is a local low-magnification tissue photograph (side view) after step five in Example 1 of the present invention is completed.
[0027] Figure 5 This is a local low-magnification tissue photograph (frontal perspective) after the completion of step five in Example 1 of the present invention.
[0028] Figure 6 This is a high-magnification tissue photograph of the normal area after step five in embodiment 1 of the present invention is completed.
[0029] Figure 7 This is a high-magnification tissue photograph of the bright spot area after step five in embodiment 1 of the present invention is completed. DETAILED DESCRIPTION
[0030] The following is further described in detail through specific implementation methods: Embodiment 1 Embodiment 1: A method for evaluating the uniformity of the composition of a titanium alloy ingot comprises the following steps: Step 1: High temperature solid solution in single phase region, heat the ingot riser to T β + (10-300) °C, keep warm and then cool rapidly, the keeping time T1 = D × (0.5-3.0) minutes, where D is the thickness of the riser in mm; in addition, the rapid cooling method in this step adopts water cooling, and the water is cooled to room temperature.
[0031] Step 2: First stage low temperature aging: cool the ingot to room temperature in step 1 to a temperature of T β - (200 ~ 400) below the temperature, the temperature is kept for 1 ~ 8 hours, and then the ingot riser is heated to T β - (30 ~ 60) ℃, cool after keeping warm, the keeping time T2 = D × (0.5 ~ 3.0) minutes, where D is the thickness of the riser, the unit is mm, and the cooling method is air cooling.
[0032] Step 3: β spot heat treatment: the ingot riser after air cooling in step 2 is placed at T β The temperature is kept at -25℃ for 2h and then cooled by water.
[0033] Step 4, second stage low temperature aging, the ingot riser after water cooling in step 3 is kept at 600-650°C for 4-8h, and then cooled by air cooling.
[0034] Step 5: High and low magnification tissue detection.
[0035] Specifically, in this embodiment, a typical TC17 titanium alloy is used as an example. The nominal composition of the TC17 titanium alloy is Ti-5Al-4Mo-4Cr-2Sn-2Zr, and the empirical average β transformation temperature is 895°C (i.e., T β The value is 895℃), the process steps are as follows: Step 1: Single-phase high-temperature solid solution, heat the ingot riser with a size of Φ620×50mm (i.e., the diameter of the ingot riser is 620mm and the thickness is 50mm) to 930℃ (i.e., T β +35℃), keep warm for 120min and then cool with water.
[0036] Step 2: First stage low temperature aging: the ingot riser after water cooling to room temperature in step 1 is heated to 630°C (T β -295℃) for 2h, and then heat the ingot riser to 850℃ (T β -45℃), keep warm for 120min and then air cool.
[0037] Step 3: β spot heat treatment: the ingot riser cooled in step 2 is heated to 870℃ (T β -25℃) for 2h and then water-cooled.
[0038] Step 4: Second stage low temperature aging: age the ingot riser after water cooling in step 3 at 630°C for 8h, and then air cool.
[0039] Step 5: High and low magnification tissue detection.
[0040] Comparative Example: The conventional finished bar was tested at low magnification and high magnification, and the test results are as follows: Figure 4-Figure 6 shown.
[0041] according to Figure 1 and Figure 2 It can be seen from the comparison that in this embodiment, after step one and step two, an equiaxed / short rod α phase similar in morphology to the finished rod but smaller in size has appeared in the original cast structure, and the basic conditions for β spot detection have been met.
[0042] Combination Figure 3-Figure 7 It can be seen that according to the low-power and high-power tissue photos, Figure 6 The α phase content in the normal area is still 9.4%, while there is no α phase in the bright spot area, which can generally be judged as a β spot. It can be seen that the uniformity of the composition of the titanium alloy ingot can be easily judged.
[0043] In this embodiment, the composition of the ingot riser after step 4 is detected, and the composition of the normal area and the bright spot area is analyzed using a three-dimensional atomic probe. Two positions are taken in the normal area and the bright spot area for detection. The analysis results of each alloy element are shown in Table 1. According to the detection results in Table 1, it can be seen that obvious Cr element enrichment appears in the bright spot area, which confirms that the bright spot is caused by the segregation of the Cr element, indicating that the present process can accurately detect the β spot of the ingot, which is convenient for evaluating the composition uniformity level of the ingot.
[0044] Element Type Al Mo Cr Sn Zr Normal area 1 4.33 4.43 4.01 2.22 1.97 Normal area 2 4.43 4.16 4.18 2.34 1.88 Bright spot area 1 4.21 4.51 4.55 2.01 2.09 Bright spot area 2 4.27 4.22 4.72 2.26 2.01 Table 1 Elemental analysis results The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A method for evaluating the composition uniformity of a titanium alloy ingot, comprising the following steps: Step 1: High temperature solid solution in single phase region, heat the ingot riser to T β + (10~300)℃, rapid cooling after heat preservation; Step 2: First stage low temperature aging: the ingot riser cooled in step 1 is placed at T β - Keep warm below (200~400), then raise the temperature to T β - (30~60)℃, keep warm and then cool; Step 3: β spot heat treatment: the ingot riser cooled in step 2 is placed at T β Keep warm at -25℃ and then cool; Step 4: Second stage low temperature aging, the ingot riser after water cooling in step 3 is kept at 600-650°C and then cooled; Step 5: High and low magnification tissue detection.
2. A method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 1, the insulation time of the ingot riser is T1=D×(0.5-3.0) minutes, where D is the thickness of the ingot riser in mm.
3. A method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 2, the ingot riser is at T β -The holding time at (200~400)℃ is 1~8h.
4. A method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 2, the ingot riser is heated to T β -After (30~60)℃, the holding time T2 = D×(0.5~3.0) minutes, where D is the thickness of the ingot riser, in mm.
5. The method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 3, the ingot riser is at T β The holding time at -25°C is 2h.
6. A method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 4, the ingot riser is kept at a temperature of 600-650° C. for 4-8 hours.
7. A method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: The rapid cooling method in step 1 is water cooling.
8. The method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 2, the ingot riser is heated to T β - (30~60)℃ insulation and cooling method is air cooling.
9. A method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 3, the ingot riser is at T β After keeping at -25℃, the cooling method is water cooling.
10. The method for evaluating the composition uniformity of a titanium alloy ingot according to claim 1, characterized in that: In step 4, the ingot riser is kept at 600-650° C. and then cooled by air.
Citation Information
Patent Citations
Method for inspecting nonuniformity of low power structure of titanium alloy
CN103852360A
Method for manufacturing TC18 titanium alloy whole basket-weave microstructure medium-specification ultra-long bars
CN104762576A
Method for measuring phase transformation point temperature of beta single-phase region titanium alloy through recrystallization
CN112051294A
Method for judging whether near-beta titanium alloy has beta spot defect or not
CN113624793A
Method for evaluating microcosmic component uniformity of easily segregated titanium alloy cast ingot
CN114908306A